Democratic Governance in Mexico : Beyond State Capture and Social Polarization - World Bank (Washington, DC, 2012)
Mexico is in the midst of a transition. The defeat of the Revolutionary Institutional Party (PRI) in the 2000 presidential election marked a watershed, and with the repeated defeat of the PRI in the 2006 election, the era of the single?party dominance appears to be long gone. The demise of the one?party system may have been expected to usher in a new era where benefits of the government policies and economic development are more widely shared. But, such a change has yet to take place. Why not? At the same time, there is a strong perception that the pace of much?needed economic reforms slowed down under the new political arrangement. Why? This Institutional and Governance Review (IGR) addresses these crucial questions, and in so doing tries to offer some insights into how Mexico's democratic governance may be strengthened over time. Taking into consideration the evidence collected for this work, the study argues that Mexico is well positioned to start its second transition towards effective democratic governance in the country, but to do so will require addressing certain socio-political obstacles that continue to limit the full effects of democratic accountability.